Survival and Prognostic Factors Predicting Outcomes of Patients with Primary Non-Metastatic Colorectal Cancer who have not had Curative Intervention - Mariam Rizk (World Journal of Colorectal Surgery)
Background: The natural progression and life expectancy of patients following a diagnosis of treatable colorectal cancer who receive only symptomatic treatment, nonoperative palliative therapy, or noncurative surgical interventions are relatively unknown.